Relationship between chronological age and skeletal maturity of wrist joint and hand in a sample of Nepalese population: A radiographic study of wrist joint and hand in Nepalese population: A radiographic approach - Parajuli, Sudhir Raman; Gautam, Rabin; Timsinha, Sidarth; Sharma, Prakash (Journal of Kathmandu Medical College, 2021)
Background: The human body grows and matures with age, especially in children and adolescents. Skeletal age is determined from the development stage of bones.Objectives: To determine the age of epiphyseal fusion of the lower end of radius and ulna in the Nepalese population which is important from a medicolegal point of view.Methods: An analytical cross-sectional study was conducted on patients undergoing X-rays of hand and wrist attending Manipal Teaching Hospital, Pokhara in a one-year period from January 1, 2019 to December 31, 2019. Total sample was 90 cases. The X-rays were assessed as appearance and not-appearance of epiphysis and different phases of skeletal maturity were graded according to McKern and Stewart classification.Results: Mean age was relatively higher in males in fusion of radius. Whereas in ulna, no difference was recorded in mean age in the fifth stage. In male the correlation coefficient for stage of fusion for radius and ulna with age (years) was 0.90 and 0.65 (p < 0.001), while for the females the correlation coefficient for stage of fusion of radius and ulna with age was 0.94 and 0.82 (p